2000
DOI: 10.1002/1521-396x(200010)181:2<479::aid-pssa479>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Magneto-Optical Properties of MnSb Films Grown on Sapphire Substrate

Abstract: We have grown MnSb films on sapphire substrates by hot wall epitaxy. A series of films with thicknesses of 80, 155 and 230 nm was prepared to determine the thickness dependence of their magnetic and magneto-optical properties. Our results indicate that the thinnest and thickest films possess largest coercivity and saturation magnetization, respectively. The largest Kerr rotation angle was also found in the thickest film for both the longitudinal and polar Kerr rotations, reaching a maximum of 0.31 . We attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Due to compatibility with conventional III-V semiconducting materials, thin films of pure MnSb have been intensively studied as a perspective material for creation of efficient FM/semiconductor heterostructures. In relevant works, MnSb films were usually obtained from the elemental sources using molecular-beam 35 40 and hot-wall 41 44 epitaxy techniques. As an alternative, several groups studied films obtained via layer-by-layer Mn-Sb deposition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to compatibility with conventional III-V semiconducting materials, thin films of pure MnSb have been intensively studied as a perspective material for creation of efficient FM/semiconductor heterostructures. In relevant works, MnSb films were usually obtained from the elemental sources using molecular-beam 35 40 and hot-wall 41 44 epitaxy techniques. As an alternative, several groups studied films obtained via layer-by-layer Mn-Sb deposition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for MnSb films, obtained using hot-wall epitaxy technique, an increase of crystallinity, induced by an increase of substrate temperature 43 , results in an increase of coercive force, , and a decrease of values. Thinner MnSb films reveal small compressive strain of crystal structure, which becomes negligible as the film thickness (deposition time) is increased 42 , 44 . Different groups reported that increased deposition time result in an increase 44 or a decrease 42 of mean crystallite size, while in both cases it leads to a decrease of and an increase of values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation